2015
DOI: 10.1016/j.chom.2015.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella Manipulation of Host Signaling Pathways Provokes Cellular Transformation Associated with Gallbladder Carcinoma

Abstract: Cancer is fueled by deregulation of signaling pathways in control of cellular growth and proliferation. These pathways are also targeted by infectious pathogens en route to establishing infection. Gallbladder carcinoma (GBC) is frequent in the Indian subcontinent, with chronic Salmonella enterica serovar Typhi infection reported as a significant risk factor. However, direct association and causal mechanisms between Salmonella Typhi infection and GBC have not been established. Deconstructing the epidemiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
213
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 210 publications
(233 citation statements)
references
References 51 publications
7
213
0
1
Order By: Relevance
“…A recent study demonstrated that S. enterica serovar Typhi infection of the gallbladder was sufficient to cause gallbladder carcinoma (GBC) in genetically predisposed cells. This association was investigated after the identification of an overlap in populations at risk for both typhoidal infection and GBC, with a high occurrence of both diseases in India (134). Scanu et al demonstrated that bacterially mediated AKT and mitogen-activated protein kinase (MAPK) activation is required for the initiation of cellular transformation and tumor growth but is not required for sustained tumorigenesis, a conclusion concordant with previously reported hypotheses linking bacterially mediated downregulation of apoptosis and cancer initiation (135).…”
Section: Salmonella Bile Resistance Mechanismssupporting
confidence: 65%
“…A recent study demonstrated that S. enterica serovar Typhi infection of the gallbladder was sufficient to cause gallbladder carcinoma (GBC) in genetically predisposed cells. This association was investigated after the identification of an overlap in populations at risk for both typhoidal infection and GBC, with a high occurrence of both diseases in India (134). Scanu et al demonstrated that bacterially mediated AKT and mitogen-activated protein kinase (MAPK) activation is required for the initiation of cellular transformation and tumor growth but is not required for sustained tumorigenesis, a conclusion concordant with previously reported hypotheses linking bacterially mediated downregulation of apoptosis and cancer initiation (135).…”
Section: Salmonella Bile Resistance Mechanismssupporting
confidence: 65%
“…Additionally, S. Typhi gastrointestinal infection can facilitate gallbladder colonization and long-term carriage in 3 to 5% of infected individuals (47). Gallbladder carriage has been shown to be a result of biofilm formation on gallstones and the gallbladder epithelium and to increase the risk for gallbladder carcinoma (21,48,49). Bile enhances Salmonella biofilm formation on gallstone surfaces, implicating a bacterial response to bile that promotes persistence (50,51).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to an NFκB-induced inflammatory response, the authors observed disruption of epithelial tight junctions and downregulation of ISC markers Lgr5 and Bmi1 in Salmonella-infected organoids (Zhang et al, 2014). Neefjes and colleagues recently exploited co-cultures of adult stem cell-derived gallbladder organoids with Salmonella enterica to determine the effects of infectious pathogens on the development of cancer (Scanu et al, 2015). Utilizing pre-transformed gallbladder organoids derived from mice deficient for the Ink4a/Arf (Cdkn2a) tumor suppressor locus, the authors found that Salmonella induces growth factor-independent growth and neoplastic transformation through activation of AKT and MAPK signaling (Scanu et al, 2015).…”
Section: Host-pathogen Interactionsmentioning
confidence: 99%
“…Neefjes and colleagues recently exploited co-cultures of adult stem cell-derived gallbladder organoids with Salmonella enterica to determine the effects of infectious pathogens on the development of cancer (Scanu et al, 2015). Utilizing pre-transformed gallbladder organoids derived from mice deficient for the Ink4a/Arf (Cdkn2a) tumor suppressor locus, the authors found that Salmonella induces growth factor-independent growth and neoplastic transformation through activation of AKT and MAPK signaling (Scanu et al, 2015). Likewise, adult stem cell-derived human stomach organoids have been used to study Helicobacter pylori infections.…”
Section: Host-pathogen Interactionsmentioning
confidence: 99%